Social determinants of stage IV anal cancer and the impact of pelvic radiotherapy in the metastatic setting. (4th October 2017) - Repka, Michael C.; Aghdam, Nima; Karlin, Andrew W.; Unger, Keith R.
Abstract: Anal cancer is a relatively rare malignancy, and a minority of patients present with metastatic disease in the United States. The National Cancer Database (NCDB) was used to identify factors associated with metastatic disease at presentation and evaluate the role of pelvic radiotherapy in these patients. The NCDB was queried for patients with squamous cell cancer of the anus diagnosed between 2004 and 2013. Patients were stratified by clinical stage at diagnosis, and a binary logistic regression model was created to identify factors associated with metastatic disease at diagnosis. A secondary metastatic cohort was generated and a multivariable Cox proportional hazards model was created to identify factors associated with improved survival. To validate findings, propensity‐score matching was performed to generate a 1:1 paired dataset stratified by receipt of pelvic radiotherapy. The primary analysis cohort consisted of 28, 500 patients. Facility location, male gender, and lack of insurance were confirmed as independent risk factors for metastatic disease. The metastatic cohort consisted of 1264 patients. Multivariable analysis confirmed female sex, possession of a private or Medicare insurance plan, pelvic radiotherapy, and chemotherapy as independent predictors of improved survival. A propensity‐score matched cohort of 730 patients was generated. The median survival was 17.6 months in patients who received radiotherapy versus 14.5 months in those who did not ( P  < 0.01). In this cohort, male gender and lack of insurance were associated with metastatic disease at presentation. Furthermore, a significant benefit was associated with the use of pelvic radiotherapy. Future prospective research is warranted to confirm these findings. Abstract : Using the National Cancer Database, male gender, facility location, and lack of insurance were associated with metastatic disease at presentation. Furthermore, a significant benefit was associated with the use of pelvic radiotherapy in these patients.